PROBLEMATIKA PENERAPAN KURIKULUM MERDEKA BELAJAR PADA KELAS IV DI SD NEGERI 6 BINTAUNA - Pangkey, Richard; Sarinaung, Elsa (DIKSAR : Jurnal Pendidikan Dasar, 2023)
The results showed that: First, the implementation of the independent curriculum at SD Negeri 6 Bintauna Class IV applies the Pancasila student profile with project-based learning, subject-based learning, IPAS. Second, the problems faced by arranging learning tools such as CP, TP, ATP, and teaching modules, difficulty determining learning strategies and methods, limited student books, teaching materials that are too broad, determining class projects that are in accordance with the learning material, determining assessments that match the material. Third, the efforts made by teachers in the problem of implementing the independent curriculum in grade IV SD Negeri 6 Bintauna by attending meetings with KKG, attending training, writing material on the board, students taking notes, continuing class projects at home, seeking information about assessments and attending training on the implementation of the Independent Learning CurriculumThe independent learning curriculum has been implemented at SD Negeri 6 Bintauna since 2022/2023 in stages. In its application, it is inseparable from problems both in planning, implementation, and assessment. Therefore, the research aims to: 1). Know the application of the independent learning curriculum in grade IV at SD Negeri 6 Bintauna, 2). Know the problems in the application of the independent learning curriculum in grade IV SD Negeri 6 Bintauna 3). Know the efforts made in overcoming problems with the implementation of the independent learning curriculum in grade IV SD Negeri 6 Bintauna. This research is a qualitative description research. The data collection process was carried out using observation, interview and documentation techniques. Data analysis carried out by researchers uses data reduction methods, data presentation, and conclusion drawing